2006
DOI: 10.1002/pros.20514
|View full text |Cite
|
Sign up to set email alerts
|

Antibody array profiling reveals serum TSP‐1 as a marker to distinguish benign from malignant prostatic disease

Abstract: The measurement of thrombospondin-1 could be used to assist the decision to obtain a biopsy in men with suspected prostate cancer, which could lead to a reduction in the number of unnecessary prostatic biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 41 publications
0
38
0
Order By: Relevance
“…Examples include identification of disease signatures based on detection of multiple cytokines and inflammatory mediators [2][3][4]10,12,[20][21][22][23][24]. The results are commonly validated by independent assays such as ELISA and Western mediators [2][3][4]10,12,[20][21][22][23][24][25][26][27] (Table 1). In several cases, samples have been spiked with recombinant proteins to test specificity of the binders directly in the application (Table 1).…”
Section: Can Monospecific Binders Be Made?mentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include identification of disease signatures based on detection of multiple cytokines and inflammatory mediators [2][3][4]10,12,[20][21][22][23][24]. The results are commonly validated by independent assays such as ELISA and Western mediators [2][3][4]10,12,[20][21][22][23][24][25][26][27] (Table 1). In several cases, samples have been spiked with recombinant proteins to test specificity of the binders directly in the application (Table 1).…”
Section: Can Monospecific Binders Be Made?mentioning
confidence: 99%
“…The assay format is simple; the labelled sample is layered onto the slide, unbound protein is removed, and the captured proteins are detected using a fluorescence scanning device. Antibody arrays were later used to detect protein expression signatures in serum from patients with pancreatic cancer, lung cancer and prostate cancer [2][3][4]. Because then, several groups have joined the field, and the technology has been developed to a new level of sophistication.…”
Section: Introductionmentioning
confidence: 99%
“…Antibody array profiling has also identified possible serum markers, such as thrombospondin-1, that may differentiate between benign and malignant disease. 141 Increased antibody titers of antiproteasome and anti-huntingtin interacting protein-1 have been associated with the presence of CaP, 142,143 and a serum ELISA against the latter yielded a specificity of 97% when combined with an anti-AMACR test. Other autoantibody signatures may increase the discriminatory power of a screening test and are currently being evaluated.…”
Section: Pca3mentioning
confidence: 99%
“…357,358 Using antibody array profiling, Shafer et al reported serum TSP-1 could be a marker to distinguish BPH from CaP, which could lead to a reduction in the number of unnecessary prostatic biopsies. 359 Endogenous angiogenesis inhibitors are promising to treat CRPC for combination therapy with chemotherapy in the future.…”
Section: Endogenous Angiogenesis Inhibitorsmentioning
confidence: 99%